2007
DOI: 10.1093/jac/dkm484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampicin-based antitubercular therapy on nevirapine plasma concentrations in South African adults with HIV-associated tuberculosis

Abstract: Background and objectives: Nevirapine-containing antiretroviral therapy (ART) and rifampicin-based antitubercular therapy are commonly co-administered in Africa, where nevirapine is often the only available non-nucleoside reverse transcriptase inhibitor. Rifampicin induces the metabolism of nevirapine, but the extent of the reduction in nevirapine concentrations has varied widely in previous studies. We describe the steady-state pharmacokinetics of nevirapine during and after antitubercular therapy in South Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 15 publications
1
53
1
Order By: Relevance
“…A noncompartmental analysis of part of this study, including intensively sampled TB/HIV-coinfected patients (up to 12 h after nevirapine administration), has been reported earlier [17].…”
Section: Methodsmentioning
confidence: 99%
“…A noncompartmental analysis of part of this study, including intensively sampled TB/HIV-coinfected patients (up to 12 h after nevirapine administration), has been reported earlier [17].…”
Section: Methodsmentioning
confidence: 99%
“…Nevirapine biotransformation pathways are more sensitive to induction than are those of efavirenz, and nevirapine-based regimens therefore have a greater risk of subtherapeutic NNRTI concentrations. [2][3][4][5] The reduction in nevirapine concentration is most pronounced during the fi rst 2 weeks of antiretroviral therapy, when it is typically prescribed at half dose (200 mg lead-in dose) to prevent hypersensitivity before a steady state concentration has been reached. 6 To avoid this problem, WHO guidelines recommend efavirenz rather than nevirapine for patients co-infected with HIV and tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Both adult and paediatric studies done in Africa, Thailand and India have shown varying levels of the effect on NVP plasma levels as a result of the drug-drug interaction during concomitant use of a rifampicin containing anti-TB regimen and a NVP based ART regimen. [4][5][6]8,[20][21][22][23] An intensive pharmacokinetic study of standarddose NVP with and without rifampicin in South African adults found sub-therapeutic NVP levels in 6 of 16 patients during rifampicin dosing. 8 A pharmacokinetic sub analysis conducted on 20 of the children in this study as reported by Barlow Mosha et al also found that NVP trough concentration was significantly reduced in children who received rifampicin and NVP concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Adult studies have demonstrated that the drug interaction between NVP and rifampicin results in decreased levels of NVP that may be suboptimal for complete viral suppression. 7,8 We conducted a retrospective analysis to compare the immunologic and virologic response to NVP based ART regimen among HIV-TB Co-infected Ugandan children on rifampicin based anti-TB treatment compared to those on ART alone.…”
Section: Introductionmentioning
confidence: 99%